Observing Techniques and Missions - Kraus, Michaela (2019)
Stellar pulsations can cause variability in the brightness of the star as well as in the shape and radial velocity of photospheric lines. To determine the periods and modes of pulsations, two different but complementary observational techniques are in use: photometric light curves to measure the brightness variations, and spectroscopic time series to analyze the time-dependent motions at the stellar surface. In the first part of this Chapter, both observing techniques and their sources of errors and limitations are presented. In the second part, an overview of the various space and ground-based missions for both photometry and spectroscopy is given. Considering all the currently available and newly planned instruments, the future for research in variable and pulsating stars is bright.